Approach to the Patient with Resistance to Thyroid Hormone and Pregnancy - Weiss, Roy E. (The Endocrine Society, 2010)
Resistance to thyroid hormone (RTH), a syndrome of reduced end-organ responsiveness to thyroid hormone (TH), is mostly caused by mutations in the TH receptor (TR) β gene. Diagnosis is based on persistent elevations of serum free T(4) and often T(3) levels in the absence of TSH suppression, and confirmation in most cases is by way of genetic testing. The mainstay in the management of RTH patients who are asymptomatic is to recognize the correct diagnosis and avoid antithyroid treatment. Deciding whether to manage these patients with TH replacement is made even more challenging when an affected individual is pregnant. How one approaches such a patient with pregnancy and RTH would depend on the genotype of the fetus. This requires obtaining prenatal information on the genotype of the fetus and a thorough history of the outcome of previous pregnancies as well as a history of the course and outcome of other family members with RTH. If the TRβ mutation is known in the mother, the fetus can be rapidly genotyped from DNA from amniocentesis for the same mutation, and then management decisions could be made regarding thyroid or antithyroid hormone treatment.